Lived Time in Moments of Unease: Responsibility and Genuine Time in Professional Practice - Helene Thorsteinson; Tone Saevi (University of Bologna, 2023)
Moments of moral disquiet encounter clock time as well as lived time, and thus professional human practices are existential and take place in time and space. Professional practices as existential involve human bodies and relationships, and are based on trust, responsibility, and vulnerability. The paper explores the relation between lived time and moments of disquiet. We borrow lived experience descriptions from students in professional practices and analyse them phenomenologically. Our informants are students in profession studies of nursing, social work and education interviewed individually in or after external institutional practice during their education. In the interviews they share their experiences of personal responsibility in situations orienting to others in professional practices. As a life existential, time shapes and organises our bodies and activities from birth to grave and is lived and experienced in a variety of ways in daily life and life as such. Time is thus a precondition of human life and life itself. Our interest in this paper is to show and argue phenomenological-pedagogically why and how it is of professional significance to teach students to take the required time to care, and to encourage them to be attentively present in situations when other persons' lives take place.